Calidad de servicio y satisfacción del cliente en el Banco de la Nación ciudad de Iquitos, año 2024 - Castillo Fernandez, Yulissa Milagros (2025)
The present study aimed to determine the relationship between service quality and customer satisfaction at the Banco de la Nación in Iquitos in 2024. A descriptive correlational approach was used, with a non-experimental, cross sectional design, collecting data at a single point in time without any manipulation of variables. The sample consisted of 384 participants. The most relevant results showed a Spearman's Rho correlation coefficient of 0.711 (p = 0.000) between service quality and job satisfaction, indicating a highly positive and statistically significant relationship. This means that as the perception of service quality increases, so does staff satisfaction. Among the dimensions evaluated, empathy showed the strongest correlation with satisfaction (r = 0.717), followed by reliability (r = 0.671) and responsiveness (r = 0.669), revealing that the human aspects of service play a considerable role in the internal customer experience. It is concluded that improving perceived service quality not only benefits external users but also strengthens employee engagement and well-being, creating a more efficient and supportive environment. These findings provide valuable evidence for human talent management and continuous improvement in the public banking sector.